PARIWISATA DIGITAL: PERSPEKTIF DAN AGENDA RISET MASA DEPAN - Ernawati, Hani; Hananto, Kombang (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2023)
Digital tourism is a new approach to the tourism experience that provides digital support to tourists before, during, and after tourism activities. This support allows tourists to pour back all of their experiences of traveling in the real world into the digital dimension, blurring the boundaries between tourism and gaming. The purpose of this study is to explore the meaning of digital tourism and provide a research agenda for digital tourism. The study's results reveal the latest developments in digital tourism research, which focus on understanding the impact of digital technology on the tourism industry and identifying trends and opportunities for the tourism business. One of the research objectives is to investigate how digital tourism experiences can attract tourists to visit tourist sites, allowing operators and stakeholders of tourist sites to use new ways to enhance the digital tourism experience. The study also examines the trends and research objectives of digital tourism over the last three decades. The integration of new technologies in the tourism sector has made digital tourism a powerful and economically relevant sector. The internet and digital solutions, in general, are becoming increasingly relevant and widespread in this sector. The study's research agenda aims to provide insights to enhance the digital tourism experience and identify new opportunities for the tourism industry. The study's findings can be used by tourism operators and stakeholders to develop new strategies and technologies to enhance the digital tourism experience.